Quality Testing of Solid Soap with Mango Leaf Extract (Mangifera indica L.) Produced by Hot and Cold Processes - Karimah, Zulfa Nurul; Kristiana, Riska (Proceeding International Conference on Science and Engineering, 2020)
Mango leaves (Mangifera indica L.) contain alkaloids, flavonoids, stereoid compounds, polyphenols, tannins and saponins. The saponin content in mango leaves is able to act as a natural foaming agent. Mango leaf extract can be added in the manufacture of solid soap to produce natural soap. Making solid soap can be done through heating (heat process) and without heating (cold process). This study aims to determine the process of making solid soap in a hot and cold process, comparing the best quality soap analysis based on quality including organoleptic testing and pH balance. The results showed the average quality of the best soap through the heat process with the results of organoleptic tested.